Optimization of The Amount of Chickpea Sourdough and Dry Yeast in Wheat Bread Formulation: Evaluation of Physicochemical, Sensory and Antioxidant Properties - Ertop, Muge Hendek; Seker, Ibrahim Tugkan (Japanese Society for Food Science and Technology, 2018)
The aim of this study was to optimize amounts of chickpea sourdough (A) and instant active dry yeast (B) in bread formulation and to evaluate the potential use of chickpea sourdough in bread production by examining various quality parameters.An experimental design suggested by Response Surface Methodology was used.The bread produced according to the optimized model (OBrd) was compared with control bread (CBrd) in terms of several quality parameters. According to the optimization results, optimum levels of usage were 59.06 g for A and 3.39 g for B. Smaller and more homogeneous pore structures were obtained in bread (OBrd) texture by the use of chickpea sourdough according to the image analysis. The bread also acquired sour, sweetish and acceptable sensory profiles. Physicochemical properties and antioxidant activity were also improved by the use of chickpea sourdough.

WOS: 000444362200004
Keywords: Optimization; Chickpea; Sourdough; Bread; Response Surface Methodology; 2. Zero hunger